Achievement of Students' Mathematical Literacy Skills Based on Stacey's Definition Measured from the Results of the Elementary Linear Function Test - Ageng Triyono; Rusmin.R.M. Saleh; Abdul Hakim Ma’ruf; Defry Prasetyo; Wahidin Firmansyah; Arie Purwa Kusuma (LLDIKTI WIlayah XII Ambon, 2025)
This study aims to analyze the achievement of students' mathematical literacy skills based on Stacey's definition. The achievement is measured using the answers to the basic linear function test results. The objectives are achieved using a descriptive qualitative approach. The indicators of achievement of mathematical literacy skills used are that students can: understand mathematical problems (I1); apply mathematical concepts (I2); use facts to formulate mathematical problems (I3), and; present and solve mathematical problems (I4). The subjects involved in the test consisted of 33 students, and then 3 students were selected by stratified random sampling to be interviewed, where each sample represents a group of students with high (S1), medium (S2), and low (S3) mathematical abilities. The instruments used to measure are test instruments and interview guidelines. The collected data were analyzed based on the Milles & Hubberman stages. The results of the data analysis concluded that students (S1) could achieve all indicators; students (S2) could not achieve the indicators of presenting and solving mathematical problems, and students (S3) could not achieve all the indicators set. Another finding is the existence of student self-confidence that affects their mathematical literacy skills